2020
DOI: 10.3390/pr8111411
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Profiling of Forestry Waste by UPLC-HDMSE

Abstract: Polyphenols constitute a diverse array of naturally occurring secondary metabolites found in plants which, when consumed, have been shown to promote human health. Greater consumption may therefore aid in the fight against diseases such as obesity, diabetes, heart disease, cancer, etc. Tree bark is polyphenol-rich and has potential to be used in food supplements. However, it is important to gain insight into the polyphenol profile of different barks to select the material with greatest concentration and diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…These latter have been described also as constituents of other forest trees and their wastes. Indeed, recently, bulk samples of bark waste from Pinus contorta, Pinus sylvestris, and Quercus robur, were investigated in depth for their polyphenol content [27], and various biomass residues (shavings, edged cuts, and pruning wastes) from walnut were analyzed as sources of antioxidant compounds by means of a green extraction process [28]. In this context, Pycnogenol ® (PYC) and Flavangenol ® are good examples of commercially available pine bark-based products [29].…”
Section: Chemical Composition Of F Sylvatica Leaf Methanolic Extractmentioning
confidence: 99%
“…These latter have been described also as constituents of other forest trees and their wastes. Indeed, recently, bulk samples of bark waste from Pinus contorta, Pinus sylvestris, and Quercus robur, were investigated in depth for their polyphenol content [27], and various biomass residues (shavings, edged cuts, and pruning wastes) from walnut were analyzed as sources of antioxidant compounds by means of a green extraction process [28]. In this context, Pycnogenol ® (PYC) and Flavangenol ® are good examples of commercially available pine bark-based products [29].…”
Section: Chemical Composition Of F Sylvatica Leaf Methanolic Extractmentioning
confidence: 99%
“…One potential solution is the use of ultra-performance liquid chromatography (UPLC) linked to an ion mobility time-of-flight high-definition/highresolution mass spectrometer (UPLC-HDMS E ). Recent work characterising phenolic compounds in forestry waste has shown that UPLC-HDMS E can provide an in-depth analysis of the wide suite of phenolics present [8]. This is also supported by the use of UPLC-HDMS E for the detection and characterisation of bioactive compounds in complex medicinal mixtures and urine [9,10].…”
Section: Introductionmentioning
confidence: 91%
“…An experimental design was chosen (between subjects) by creating individual groups for the various plant extracts, plus one for the reference (green tea) and one group for blank extracts. As this detail has previously been published [8], only a brief overview is provided here. Post deconvolution, a 5 ppm precursor tolerance was used to compare ions to the ChemSpider Polyphenols database [13] using isotope similarity scores above 90%, an elemental composition of C, O, H only and in an silico fragmentation tolerance of 90%.…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Profiling of polyphenolics of several agro-forestry by-products by using UPLC-HDMSE was reported by Potter and Jones [7]. They used UPLC-HDMSE tool to profile ethanol extracts of three common tree barks (Pinus contorta, Pinus sylvestris, Quercus robur).…”
mentioning
confidence: 99%